A bioactive hydrogel integrating bFGF/VEGFA gene-loaded nanoparticles and platelet-rich plasma for accelerated full-thickness skin wound healing - Yan Duan; Weixin Wang; Yuanyuan Jin; Ming Jiang; Bolin Wang; Jianle Chen; Yun Jiang (PLoS ONE, 2026)
Research objectives Full-thickness skin defects present substantial challenges to the healing process, arising from the loss of the dermal layer, inadequate vascular supply, and insufficient growth factor availability. Although previous studies have established that growth factors and platelet-rich plasma (PRP) individually promote tissue repair, the synergistic benefits of their combined application for achieving superior therapeutic outcomes remain unclear. Here, we introduce a novel composite biomaterial: a hydrogel integrating nanoparticles loaded with basic fibroblast growth factor (bFGF) and vascular endothelial growth factor A (VEGFA) genes (bFGF/VEGFA NPs) with PRP (termed bFGF/VEGFA@PRP hydrogel), engineered to enable the synergistic delivery of growth factors and bioactive components. Methods In this study, we hypothesized that the bFGF/VEGFA@PRP hydrogel can promote wound healing. This hypothesis was tested through various experimental perspectives and methods including material characterization, wound healing rate, wound blood flow signal intensity, skin attachment, cell proliferation, apoptosis, collagen deposition, and growth factor levels. Results In a rat cutaneous wound model, this hydrogel accelerated wound closure, enhanced local blood perfusion, and increased the density of skin appendages and collagen fibers. Mechanistic investigations revealed upregulated expression of angiogenic factors bFGF, VEGFA, and platelet and endothelial cell adhesion molecule 1 (CD31), the anti-apoptotic protein BCL2, the cell proliferation marker Ki67, and type III collagen (COL III) in the treated group. Conclusions Collectively, these results demonstrate that the bFGF/VEGFA@PRP hydrogel promotes wound healing through the synergistic enhancement of growth factor expression, angiogenesis, and COL III deposition. The combination of gene therapy with PRP treatment was found to be more effective than either modality alone. This study establishes a promising therapeutic strategy for managing complex full-thickness skin injuries.